Impact of COVID-19 lockdown on professional soccer players` match physical activities - Rampinini, E.; Martin, M.; Bosio, A.; Donghi, F.; Carlomagno, D.; Riggio, M.; Coutts, A. J. (Science and Medicine in Football, 2021)
The COVID-19 pandemic forced the 2019-20 Italian Serie A competition to stop and players went into lockdown. During lockdown, players only trained at home, likely having a detrimental effect on players` physical fitness and capacity. This study investigated the effect of the COVID-19 lockdown on professional soccer players` match physical activities. Match activities of 265 male professional soccer players were assessed in two periods prior to (PRE1 and PRE2) and one period following the lockdown (POST) using a video tracking system. Linear mixed models were used to examine differences between-periods in total (TD), very high-speed (VHS), sprint (SPR), high-acceleration (ACC) and high-deceleration (DEC) distances, considering full match data and data from six 15-min intervals. TD and VHS during POST were lower than the two other competitive periods (p<0.001, d small-moderate). SPR did not show differences between periods (p>0.636). ACC and DEC during POST were lower than PRE2 (p<0.015, d small). Declines in most 15-min intervals after lockdown were observed in TD and VHS. There were small differences in the temporal distribution of SPR, ACC and DEC at POST. After the COVID-19 lockdown, soccer players` higher-intensity running activities were similar to those of games played before the lockdown, but TD and VHS decreased, both considering the entire match and 15-min intervals. The temporal distribution of running activities was mostly stable throughout the season.